“People Don’t Know How Lucky They Have It Here”: German-Canadian Newcomers in Sault Ste. Marie after the Second World War - Clingen, Chelsea (Ontario History)

(untitled) (The Ontario Historical Society, 2026)
Between 1946 and 1962, over 2.1 million newcomers came to the safe haven of Canada. Many of these immigrants successfully integrated into the host society. This paper will provide an intimate look into the experiences of seven families who emigrated from Germany to Sault Ste. Marie in the postwar period. In “the Soo,” cultural clubs and families of various ethnicities often banded together to help each other adapt, start over, and rebuild their lives. The resident Saultites demonstrated curiosity, but also varying degrees of acceptance of these immigrants, even though some of them had come from countries against which Canadians had fought. German newcomers to the Soo were consequently able to retain their heritage while becoming part of Canadian society. They created new identities as German-Canadians while participating in the acculturation process.